Penerapan Automatic Transfer Switch Pada Sistem Irigasi Di Desa Rejosari Kabupaten Madiun - Yuli Prasetyo; Budi Triyono; Hanifah Nur Kumala Ningrum; Raden Jasa Kusumo Haryo; Nur Asyik H.; Wisnu Muchsin (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2020)
Rejosari Village has enormous potential, namely there are many abundant rice fields around the settlement. Rejosari Village is located in Kebonsari District, Madiun Regency. Farmers in Kebonsari village have used a water pump that is used in the rice field irrigation system. However, until now many farmers still use PLN as the main source in running electric motors for irrigation systems. So that farmers often experience power outages due to lack of electrical power. Community service activities through a partnership program for farmer groups in Rejosari Village, Kebonsari District, Madiun Regency are focused on making Automatic Transfer Switch (ATS) panels to convert electrical energy source switches from PLN to sources of solar energy from solar panels. This ATS panel contains a switch that can replace the source of electrical energy in an electric motor that was originally from PLN into an energy source from the Solar Panel. The hope is that with this community service program, farmer groups can obtain electrical energy to power the irrigation system and not depend on PLN. This PKM can also reduce the cost of electricity rates incurred by farmers.